1997
DOI: 10.1007/978-3-7091-6858-5_16
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Comparison of Progressive and Wavelet Radiosity

Abstract: Abstract. This paper presents a comparison of basic progressive and wavelet radiosity algorithms. Several variants of each algorithm were run on a set of scenes at several parameter settings, and results were examined in terms of their error, speed, and memory consumption. We did not compare more advanced variations such as clustering or discontinuity meshing. Our results show that progressive radiosity with substructuring works fairly well for all scenes. Among wavelet methods, the Haar basis works best, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…This test scene is our hardest test scene, with lots of shadow boundaries. It is on such test scenes that higher order wavelets were behaving poorly with previous experimentations 13 .…”
Section: Computation Timementioning
confidence: 65%
See 2 more Smart Citations
“…This test scene is our hardest test scene, with lots of shadow boundaries. It is on such test scenes that higher order wavelets were behaving poorly with previous experimentations 13 .…”
Section: Computation Timementioning
confidence: 65%
“…The first test to conduct is whether higher order wavelets are giving a better visual impression. In previous tests 13 , higher order wavelets were unable to provide a correct approximation of the radiosity function, especially near shadow boundaries. Shadow boundaries are very important because they have a large impact on the visual perception of the scene.…”
Section: Visual Comparison Of Our Three Wavelet Basesmentioning
confidence: 89%
See 1 more Smart Citation
“…In practice, they have several drawbacks, especially in terms of memory costs. In the early implementations of wavelets bases in the radiosity algorithm, these negative points were overcoming the positive theoretical advantages [19]. Recent research [7] has shown that using new implementation methods [2,3,7,18,21] we can actually exploit the power of higher order wavelets, and that their positive points are now largely overcoming the practical problems.…”
Section: Previous Workmentioning
confidence: 99%
“…Due to the complexity of the algorithms and data structures (by definition we are working with very complex models), no experimental analysis of the behavior of clustering algorithms has been undertaken today. Willmott and Heckbert 15 provided an inspiring study for progressive refinement radiosity and hierarchical radiosity without clustering, but evidently this study was restricted in the type of scene considered.…”
Section: Introductionmentioning
confidence: 99%